2012
DOI: 10.1002/jbio.201200072
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric measurements of human tissues for the detection of subjacent blood vessels in an endonasal endoscopic surgical approach

Abstract: Thin slices of human tissues are characterized concerning reflection and transmission in a wavelength range from 400 to 1700 nm. The results are primarily useful to find a wavelength for the detection of subjacent blood vessels during surgical procedures, especially neurological surgery. The measurements have been conducted using a customized measuring station, utilizing two halogen bulb lamps and two spectrometers. This paper focuses on creating a data base with the optical properties of artery, brain, bone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…13 The unfiltered radiation was then coupled out of the endoscope cable and freespace radiated onto the tissue's surface (2), where the diameter of the spot was 10 AE 1 mm. 13 The unfiltered radiation was then coupled out of the endoscope cable and freespace radiated onto the tissue's surface (2), where the diameter of the spot was 10 AE 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…13 The unfiltered radiation was then coupled out of the endoscope cable and freespace radiated onto the tissue's surface (2), where the diameter of the spot was 10 AE 1 mm. 13 The unfiltered radiation was then coupled out of the endoscope cable and freespace radiated onto the tissue's surface (2), where the diameter of the spot was 10 AE 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…For vascular structures (eg, veins, arteries), where classification performance was relatively poor in our study, the addition of multispectral signatures from blood flow is expected to improve classification accuracy. 4,5 For other tissue types, it is uncertain how the adjustment from cadavers to live humans will affect the real-world performance of the ML models. A relatively small image database was recorded for this study, which may result in overfitting of the ML model and hinder generalization of the model’s performance to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Multispectral imaging has emerged as a promising tool to noninvasively identify tissue composition through measurement of the tissue’s absorption, reflectance, and fluorescence spectra across visible and nonvisible wavelengths of light 1 . Foundational studies have demonstrated its discriminant power for various tissues, including blood vessels, bone, fat, muscle, nerve, and skin 2–6 . Potential applications have previously been explored across various fields of medicine, including gastroenterology, 7 , 8 laparoscopic surgery, 9 gynecology, ophthalmology, neurosurgery, critical care, cardiology, 10 and otolaryngology–head and neck surgery 6,11–15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical properties of living tissue are important for many diagnostic methods in the field of biomedical optics and biophotonics 1,2 and light scattering often limits the ability to analyze cellular structures. 3,4 Scattering in biological tissue occurs mainly in the forward direction with the resulting angle-dependent intensity distribution being determined by the structure size, the refractive index, and the geometry of the structures.…”
mentioning
confidence: 99%